2021
DOI: 10.1002/chem.202102051
|View full text |Cite
|
Sign up to set email alerts
|

Design of Stimuli‐Responsive Dynamic Covalent Delivery Systems for Volatile Compounds (Part 2): Fragrance‐Releasing Cleavable Surfactants in Functional Perfumery Applications

Abstract: Amphiphilic imines prepared by condensation of a hydrophobic fragrance aldehyde with a hydrophilic amine derived from a poly(propylene oxide) and poly(ethylene oxide) diblock copolymer were investigated as cleavable surfactant profragrances in applications of functional perfumery. In water, the cleavable surfactants assemble into micelles that allow solubilization of perfume molecules that are not covalently attached to the surfactant. Dynamic headspace analysis on a glass surface showed that solubilized perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Giuseppone and co-workers reported that aldehydes, which are components of fragrances, attach to the terminal amine of polyethylene glycol-polyphenylene oxide surfactants to form micelles and that the fragrance components are released from the micelles when hydrolysis proceeds under specific pH conditions [ 54 ]. When various oil components were solubilized as fragrances, the more volatile oil components were more easily retained inside the micelles, and evaporation of the less volatile components was accelerated [ 55 ]. This is an interesting example of how the balance of release of solubilized fragrance components can be controlled.…”
Section: Response Of Supramolecular Self-assembly To Stimulimentioning
confidence: 99%
“…Giuseppone and co-workers reported that aldehydes, which are components of fragrances, attach to the terminal amine of polyethylene glycol-polyphenylene oxide surfactants to form micelles and that the fragrance components are released from the micelles when hydrolysis proceeds under specific pH conditions [ 54 ]. When various oil components were solubilized as fragrances, the more volatile oil components were more easily retained inside the micelles, and evaporation of the less volatile components was accelerated [ 55 ]. This is an interesting example of how the balance of release of solubilized fragrance components can be controlled.…”
Section: Response Of Supramolecular Self-assembly To Stimulimentioning
confidence: 99%
“…In this scenario, Schiff bases (SB) represent valid profragrances that can be synthesized starting from odorant aldehydes and primary amines through a condensation reaction [ 14 , 15 , 16 ]. The reaction is reversible, and the SB can be readily hydrolyzed to the starting materials in aqueous environments, mainly in acidic conditions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of reversible covalent bonds is being explored in different fields for multiple purposes (Huang et al, 2020) including the design of smart release systems of bioactives (Chen et al, 2020;Fadida, Selilat-Weiss, & Poverenov, 2015;Rizzo & Kehr, 2021;Tchakalova et al, 2021;Zentner, Anson, Thayumanavan, & Swager, 2019).…”
Section: Introductionmentioning
confidence: 99%